2009
DOI: 10.1186/1471-2407-9-431
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and expression of CDw75 antigen in human colorectal cancer

Abstract: BackgroundIncreased ST6Gal I activity has been associated with the α(2,6)sialylation enhancement of membrane glycoconjugates observed in metastatic colorectal carcinomas (CRC). Siaα(2,6)Galβ(1,4)GlcNAc sequence, known as CDw75, is a sialylated carbohydrate determinant generated by the ST6Gal I. This epitope has been reported to be associated with the progression of gastric and colorectal tumours, hence there are only a few conclusive studies to date.MethodsBy radioisotopic techniques we evaluated the ST6Gal I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The expression detected in this tissue could be related to the tumour process since we have not observed expression of CDw75 in colorectal mucosa from disease-free patients. Concerning the colorectal adenomas, we detected expression of CDw75 antigen in 26% of the specimens, similar to our previous observations [22] in a study in which a smaller number of adenomas were analyzed. The majority of the adenomas showed weak CDw75 expression and the correlation analysis between the expression and the clinicopathological features did not reveal any association.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The expression detected in this tissue could be related to the tumour process since we have not observed expression of CDw75 in colorectal mucosa from disease-free patients. Concerning the colorectal adenomas, we detected expression of CDw75 antigen in 26% of the specimens, similar to our previous observations [22] in a study in which a smaller number of adenomas were analyzed. The majority of the adenomas showed weak CDw75 expression and the correlation analysis between the expression and the clinicopathological features did not reveal any association.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, we reported enhanced CDw75 expression in CRC specimens compared with healthy colorectal specimens [22] . The main objective of this work was to study the influence of CDw75 expression in tumour recurrences in patients with CRC.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The CDw75 antigen is a ligand for the leukocyte adhesion receptor cluster of differentiation (CD) 22, whose activation leads to the inhibition of intracellular signaling pathways (5). CD22 is located on the B cell membrane and specifically recognizes α(2,6)-linked sialic acid (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in CRC patients, ST6Gal I activity is greater in tumor than in healthy tissue (18,19), particularly in metastatic tumors (20). The CDw75 antigen is expressed in the majority of colorectal tumors, where its expression is augmented with regard to the healthy mucosa (21,22). Additionally, CDw75 expression is particularly high in non-polypoid tumors and advanced or metastatic stages of the disease, although results from clinicopathological studies suggest it could represent a good prognosis marker for 3-year overall survival (23).…”
Section: Introductionmentioning
confidence: 99%